QuoVadis Regulation of Islamic Economics in Post-Reform Indonesia - Apik Anitasari Intan Saputri (GoAcademica Research & Publishing, 2020)
This paper describes the regulation of Islamic economics and the urgency of its development, the post-reform Islamic economic, regulatory system, and analyzes the orientation of Indonesian Islamic economic regulation from a political economy perspective. This article's method is a descriptive analysis by analyzing political phenomena that occur in the formulation of Islamic economic regulations in post-reform Indonesia. This qualitative research uses literature studies. The development of Islamic financial regulation in Indonesia is relatively late when referring to Islamic finance development in other countries. This is related to the national political conditions, which are generally less responsive to institutions labeled Islamic. The dramatic changes in Indonesian politics since the fall of the Soeharto regime have made room for real democracy. Islamic banking regulation responds to the Islamic banking industry's development, which requires assurance of legal certainty and legal justice in a clear regulation. The increase in the role of the government in dealing with Islamic economic problems has a big role. According to Islam, economic policies must be supported by social responsibility, limited economic freedom by sharia, multi-ownership recognition, namely private ownership, state ownership, and a high work ethic. The interpretation and development of Islamic economic regulations can be richer and more important if it is based on concrete experiences of development in implementing Islamic economic regulations in Indonesia. In seeking economic laws in line with the rububiyah principle, practical experiences are material for validating Islamic economic laws.